Estudio de la calidad del servicio de provisión de agua potable que presta el Gobierno Autónomo Descentralizado Municipal del Cantón Balsas, en la parroquia Balsas, año 2021. - Espinoza Salazar, Katty Abigail (2022)
The purpose of this research project is to find out the status of the quality of the drinking water supply service provided by the Gobierno Autónomo Descentralizado Municipal del Cantón Balsas, through the application of an interview to know the perception of the service from the institutional side and another instrument such as the SERVPERF model, which was used to learn about the service from a citizen's perspective. The study is aimed mainly at the drinking water supply service. The research was based on the collection of data from an interview with 4 relevant actors based on the dimensions of quality and also based on a survey applied to 108 users, this survey was constructed based on the SERVPERF instrument, which measures the quality of service through the analysis of its five dimensions, which are: tangibility (physical facilities, equipment, materials), reliability (fulfillment of promises made to the client, right service at the right time), responsiveness (staff skills to provide quality services), security (inspire credibility and confidence in the user) and empathy (put yourself in the user's position and treat him/her as he/she deserves); Thus, the main results obtained show that the vast majority of users have a good perception of the drinking water supply service; however, some improvement measures have been proposed to help the municipality have clear ideas of the main actions to be taken to offer a 100% quality service, without unnecessary errors due to lack of staff training, thus achieving the satisfaction of service users.